DEVELOPMENT OF RENEWABLE ENERGY MARKET IN THE CONTEXT OF GLOBALIZATION CHALLENGES AND CONSTRAINTS - SHAULSKA, Larysa; TARASENKO, Liliia (Herald of Khmelnytskyi National University. Economic sciences, 2023)
The article analyzes peculiarities of the renewable energy market development in the context of globalization challenges and constraints. The research methods used иy authors are statistical analysis and synthesis, grouping, correlation, and regression analysis. Dynamics of renewable energy market development in recent years is considered, and key aspects that determine spread of various energy sources on a national and global scale are analyzed. The article proves renewable energy market growth due to development of technologies, global expansion, dissemination of knowledge and human capital, and growing attractiveness of renewable energy in private sector. It is determined that until 2007 renewable energy market was dominated by hydropower, later and nowadays solar and wind generation took the lead. Efficiency of energy generation from renewable sources in regions of the world is analyzed, as well as factors that determine position of individual countries in global renewable energy ranking. It is proved that the structure of renewable energy market varies depending on region, per 1 million. population, as well as by country. Leaders in the field of renewable energy production are identified, and key aspects that allow them to remain active market players in the future are defined. Dependence of annual electricity generation volume from renewable energy sources on the present value of energy generation from corresponding type is determined. It is proved that one of determining factors in renewable energy sector development is cost of its production, along with other significant variables. The relationship between the cost of renewable energy generation (wind and solar) and the level of its efficiency is calculated using the regression analysis method. The presence of a high influence along with other important factors is proved.